Metal–Organic Polyhedra as Building Blocks for Porous Extended Networks. Issue 11 (4th February 2022) - Khobotov‐Bakishev, Akim; Hernández‐López, Laura; von Baeckmann, Cornelia; Albalad, Jorge; Carné‐Sánchez, Arnau; Maspoch, Daniel
Abstract: Metal–organic polyhedra (MOPs) are a subclass of coordination cages that can adsorb and host species in solution and are permanently porous in solid‐state. These characteristics, together with the recent development of their orthogonal surface chemistry and the assembly of more stable cages, have awakened the latent potential of MOPs to be used as building blocks for the synthesis of extended porous networks. This review article focuses on exploring the key developments that make the extension of MOPs possible, highlighting the most remarkable examples of MOP‐based soft materials and crystalline extended frameworks. Finally, the article ventures to offer future perspectives on the exploitation of MOPs in fields that still remain ripe toward the use of such unorthodox molecular porous platforms. Abstract : Recent advances in the robustness, solubility and reactivity of metal–organic polyhedra (MOPs) have enabled their use as porous building blocks for the synthesis of extended, hierarchical porous networks. The key developments making the extension of MOPs feasible and the type and properties of the obtained porous networks are covered in this review.